Neural Suppression Elicited During Motor Imagery Following the Observation of Biological Motion From Point-Light Walker Stimuli - Grazia, Alice; Wimmer, Michael; Müller-Putz, Gernot R.; Wriessnegger, Selina C. (Frontiers in Human Neuroscience, 2022)
Introduction: Advantageous effects of biological motion (BM) detection, a low-perceptual mechanism that allows the rapid recognition and understanding of spatio-temporal characteristics of movement via salient kinematics information, can be amplified when combined with motor imagery (MI), the mental simulation of motor acts. According to Jeannerod’s neurosimulation theory, asynchronous firing and reduction of mu and beta rhythm oscillations, referred to as suppression over sensorimotor area, is sensitive to both MI and action observation (AO) of BM. Yet, not many studies investigated the use of BM stimuli using combined AO-MI tasks. Here, we assessed the neural response in the form of event-related synchronization and desynchronization (ERD/S) patterns following the observation of point-light-walkers and concordant MI, as compared to MI alone. Methods: Twenty right-handed healthy participants accomplished the experimental task by observing BM stimuli and subsequently performing the same movement using kinesthetic MI (walking, cycling and jumping conditions). We recorded electroencephalogram (EEG) with 32-channels and performed time-frequency analysis on alpha (8-13 Hz) and beta (18-24 Hz) frequency bands during the MI task. A two-way repeated measures ANOVA was performed to test statistical significance among conditions and electrodes of interest. Results: The results revealed significant ERD/S patterns in the alpha frequency band between conditions and electrode positions. Post-hoc comparisons showed significant differences between condition 1 (walking) and condition 3 (jumping) over the left primary motor cortex. For the beta band, a small significant difference in ERD patterns (p < 0.01) were only detected between condition 3 (jumping) and condition 4 (reference). Discussion: Our results confirmed that the observation of BM combined with MI elicits a neural suppression, although just in the case of jumping. This is in line with previous findings of AO and MI (AOMI) eliciting a neural suppression for simulated whole-body movements. In the last years, increasing evidence started to support the integration of AOMI training as an adjuvant neurorehabilitation tool in Parkinson’s Disease (PD). We conclude that using BM stimuli in AOMI training could be promising, as it promotes attention to kinematic features and imitative motor learning.